The Application of Dayak Customary Law In West Kalimantan Towards Fulfilling A Sense of Justice For Victims (Case Study of Indecent Acts) - Fetrus, Fetrus; Rekso Wibowo, Basuki; Yusuf Hasibuan, Fauzie (Pelopor Publikasi Akademika, 2024)
The position of customary law in the legal system in Indonesia has the same constitutional position as the legal position in general that applies in the life of the state in Indonesia. However, it must be emphasized that there is a difference between customary law and applicable law in general, namely the aspect of its enactment and formation. The applicability of customary law only applies to Indonesians and from the aspect of its form, customary law is generally not written. The method in this research uses empirical legal research. Research approaches using an empirical legal approach include a legal sociology approach, a legal psychology approach and a legal anthropology approach. Techniques for collecting legal materials through identification, inventory of positive legal rules, literature, books, journals, other sources of legal materials. Legal material analysis techniques use legal interpretation (interpretation), grammatical interpretation, systematic interpretation and legal construction methods. The results of the research and discussion show that the application of Kalimantan Dayak customary punishment is carried out by bringing together the two parties who have a conflict, then these parties are seated with traditional heads, tribal chiefs and people who are considered to understand customary law. After being seated together, a discussion was held regarding the customary offense that had occurred, whether a customary offense had indeed occurred or not. If it is known and proven that a customary offense has occurred, then the contents of the victim's demands against the perpetrator will be discussed, hereinafter referred to as customary sanctions.